Influence of One Week Education Program on the Knowledge and Approach of Pharmacy Students towards Diabetes mellitus - Shoaib Khan, Haji Muhammad; Asif, Muhammad; Qamar, Awais; ul Hassan, Ayaz; Amir, Muhammad; Murtaza, Ghulam (Acta Bioethica, 2013)
The objective of this study was to assess the improvement in knowledge and attitude of Pharmacy student towards diabetes by implementing one week long education program. Study design: Study was conducted between April 25, 2011 to April 29, 2011 which engaged the 3rd professional year Pharm. D. students comprising two groups: experimental and control groups. Lectures and visual presentations on diabetic education and practice were conducted for five days. Three surveys were performed on two groups i.e. non intervened control, non- intervened experimental and intervened experimental surveys. Questionnaire was used as survey tool comprising of 46 questions under ten categories. Results: Scores in all diabetic knowledge aspect was increased after education intervention and was significantly (P<0.05) different from that of control group. Conclusion: The marked increase in knowledge about diabetes among pharmacy students illustrates the importance of educational intervention. Educational programs may markedly increase the educational skills, efficiency and confidence of pharmacy students as well as professionals.